Microevolution and phylogenomic study of Respiratory Syncytial Virus type A - Ashfaq Ahmad; Sidra Majaz; Aamir Saeed; Shumaila Noreen; Muhammad Abbas; Bilal Khan; Hamid Ur Rahman; Faisal Nouroz; Yingqiu Xie; Abdur Rashid; Atta Ur Rehman (PLoS ONE, 2025)
Communal respiratory syncytial virus (RSV) causes mild to severe illnesses, predominantly in older adults, or people with certain chronic medical conditions, and in children. Symptoms may include rhinorrhea, cough, fever, and dyspnea. In most cases, the infection is mild and resolves on its own, but in some cases, it can lead to more serious illness such as bronchiolitis or pneumonia. The RSV genome codes for ten proteins, NS1, NS2, N, P, M, SH, G, F, M2 and L. We aimed to identify the RSV geographical transmission pattern based on parsimony and investigate hotspot regions across the complete RSV genomes. We employed Viral Evolutionary Network Analysis System on full-length available RSV genomes and with HyPhy for elucidating type of selection pressure. These results indicated that RSV strains circulating in South and North America are not mixed to the European samples, however, genomes reported from Australia are the direct decedents of European samples. Samples reported from the United Kingdom exhibited significant diversity, spanning almost every cluster. This report provides a complete mutational analysis of all the individual RSV genes, and particularly the 31 hotspot substituting regions circulating across the globe in RSV type A samples. Further, protein G and L displayed higher level of codons experienced positive selection. This analysis of RSV type A highlights mutational frequencies across the whole genome, offering valuable insights for epidemiological control and drug development.